Pengaruh Komunikasi dan Motivasi terhadap Kinerja Karyawan pada PT. Esa Garda Pratama Jakarta Selatan - Mirna Wati; Dewi Lestari (Yayasan Literasi Sains Indonesia, 2024)
This research aims to determine the effect of communication and motivation on employee performance, both partially and simultaneously. This research was conducted using quantitative research methods involving employees as samples. Various research tests used include validity, reliability, classical assumptions, correlation coefficient, regression coefficient, determination coefficient and hypothesis testing. The research results obtained the multiple regression equation Y = 6.450 + 0.564X1 + 0.270X2 + e. The regression coefficient value on the performance variable is 6.450, this shows that if communication (X1) and motivation (X2) remain constant then the performance consistency value (Y) is 6.450. Statistical test results show that there is a positive and significant influence of communication on employee performance. The t value of 6.558 is greater than the t table value of 2.011 and the significance value of 0.000 is smaller than 0.05. Thus the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted, which shows that there is a positive and significant influence of communication on employee performance. Similarly, the calculated t value for motivation is 5.253 which is greater than the t table value of 2.011 and the significance value is 0.000 which is smaller than 0.05. This shows that there is a positive and significant influence of motivation on employee performance.The calculated F value is 24.479 which is greater than the table F value of 2.800. With a significance limit of 0.05, the significance value is 0.000 which is smaller than 0.05. This means that the hypothesis states that communication and motivation variables simultaneously influence the employee's performance.